Applying ethics - Olen, Jeffrey (Thomson/Wadsworth, 2008)
From the debate over stem cell research to the heated discussions surrounding war, terrorism, and civil liberties, APPLYING ETHICS: A TEXT WITH READINGS gives you a contemporary and compelling look at the many ethical dilemmas that abound in today's world. This best-selling book introduces you to ethics through its proven formula of engaging commentary, seminal readings, and thought-provoking cases drawn from a wide range of contemporary social debates. The authors give you a basic overview of the most important ethical theories in the first chapter, with each subsequent chapter taking a current ethical issue as its focus. Guided by the authors' helpful introductions--with readings from divergent positions and particularly timely cases--APPLYING ETHICS gives you a model for considering critically some of the most controversial issues in contemporary life